2017
DOI: 10.1111/jvh.12733
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of chronic kidney disease in patients with chronic hepatitis B: A cross‐sectional survey

Abstract: Renal safety is a major concern during long-term antiviral treatment for chronic hepatitis B (CHB). This study aimed to investigate the prevalence of chronic kidney disease (CKD) in patients with CHB that had been treated with antiviral therapy. This was a single-centre, cross-sectional study in a real-life cohort in which all patients received antiviral treatment. Serum creatinine-based equations from the Chronic Kidney Disease Epidemiology Collaboration (CKD-EPI) were used to estimate the glomerular filtrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 41 publications
0
9
2
Order By: Relevance
“…One area of concern is renal function and a close association has been reported between CHB and chronic renal disease. [ 1 ] Chronic HBV infection can cause renal dysfunction through immune complex mediated glomerular diseases, such as membranous nephropathy. [ 2 ] In countries with endemic HBV infection, HBV-related glomerulopathies are an important cause of end-stage renal disease and renal replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…One area of concern is renal function and a close association has been reported between CHB and chronic renal disease. [ 1 ] Chronic HBV infection can cause renal dysfunction through immune complex mediated glomerular diseases, such as membranous nephropathy. [ 2 ] In countries with endemic HBV infection, HBV-related glomerulopathies are an important cause of end-stage renal disease and renal replacement therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Males were identi ed to be at greater risk by 77% [15]. A single-center cross-sectional study by Ning et al [16] indicated that among 1985 patients received antiviral therapy, 7.9% of whom were diagnosed with chronic kidney disease. At the same time, the diagnosis of HBV infection with renal disease not only acutely affects the prognosis of patients, but also increases the risk of death [17].…”
Section: Discussionmentioning
confidence: 99%
“…13 Epidemiological characteristics of CKD in the HBV-infected population usually vary among the different countries and areas. 14 The frequency of CKD is rather low in the USA and Western European countries, in which low prevalence rates of HBV have been reported. 4,15 In China, genotype C is the predominant HBV genotype in the northeastern region, while genotype B is in the central southern region, genotypes B and C in the southwestern region, and the recombinant genotype C/D in the northwestern region.…”
Section: Introductionmentioning
confidence: 99%
“…In China, Hou et al 14 demonstrated that hypertension, diabetes mellitus and cirrhosis were independent factors for the incidence of CKD, as determined through their singlecenter, cross-sectional study in which all patients received anti-HBV therapy. However, there are still few reports on the prevalence of CKD in patients with chronic HBV infection in the north area of China.…”
Section: Introductionmentioning
confidence: 99%